Sites of migrant landing: (un)braiding topographies of relations across hair salons in Mowbray - Mosienyane, Keamogetse (Department of Environmental and Geographical Science, 2025)
This dissertation explores hair salons in Mowbray as a node for landing amongst African migrant women who have settled in Cape Town, are arriving or in transition. To land is to set foot and to find grounding, and it is also to contend with borders. Therefore, to conceptualise the hair salon as a landing space is a deliberate geographical choice that situates landing in the central city. The significance of this is to emphasise that migrants do not land only once at national borders such as airports, shores, land ports, etc., that landing is not a singular event, and continues as African migrants try to find grounding in their new urban contexts. The dissertation's centring of the hair salon is a Black reading of space that facilitates porous mobilities through social relations and networks informed and maintained by African migrant women. Going beyond characterisations as informal trading spaces, a porous infrastructural analysis can be deployed to engage with the African hair salon as a spatial node that forefronts African women's place making in the city. The methodology for this research includes ethnographic semi-structured interviews, some of which were held during hair appointments with hairstylists, observations, archival material of Mowbray and other periodical texts. Additionally as part of the methodology, an experimentation with braiding as a cartography in Black feminist geographies provides a map of mobility in the urban space, that is routed and rooted in African women's beauty practices. Two distinct relations to the hair salon have emerged in the findings. One that emphasised place making through social relations, and the other that showed the different ways that displacement and anti-migration attitudes and policies affect the survival and maintenance of hair salons. For the former, hairstylists shared that the way they entered the hair salon market was through family and friends or a friend of a friend recommendations; the salon provides various mobility for workers who after saving up can also begin their own practices; through braiding, practices of beauty are embraced with themselves and their customers. For the latter, urban development projects such as the demolition of a long-standing shopping centre; rental increase; high inflation and unchanging prices; lack of immigration documentation were discussed in length. The hair salon stands at the intersection of community and resource building for demographics that face displacement and structural marginalisation in the city. Keywords: Black hair salon, landing, urban migration, mobility, African migrant women, arrival infrastructure, people as infrastructure, braiding as cartography, urban displacement